Health professional and at‐risk BRCA young adult perspectives about information needs: What does Gen Y need to know?. Issue 6 (19th September 2019) - Young, Alison Luk; Butow, Phyllis N.; Tucker, Katherine M.; Williams, Rachel; Healey, Emma; Wakefield, Claire E.
Abstract: Young adults at risk of a hereditary condition require the provision of accurate information to make an informed decision about genetic testing and risk management options. At‐risk young adults' (18‐ to 40‐year olds) preferences for information and resources, and genetic‐related health professionals' (GHPs) views on young adults' information needs, are largely unknown in the literature. This study aimed to clarify and compare the information needs of emerging (18‐ to 25‐year olds) and early (26‐ to 40‐year olds) adults. Resource preferences of young adults were also explored. Findings are drawn from two datasets: questionnaires and semi‐structured interviews with at‐risk young adults from BRCA1 or BRCA2 families ( N  = 32), and focus groups with GHPs ( N  = 73) working in Australian familial cancer clinics. Both datasets were analyzed using framework analysis. Emerging adults, particularly those who had not attended a clinic, wanted to know the rationale for genetic testing and basic genetic facts. Early adults were concerned about reproductive issues and cancer risk for future or current children. Information needs reported by young adults but not reported by GHPs include male cancer risk, finding reputable information, understanding test results (e.g., negative), and understanding risk terminology (e.g., lifetime cancer risk). Young adults' satisfaction with current information received was suboptimal, yet uptake of genetic‐related resources was generally low. Getting information to this cohort remains a challenge for GHPs. Emerging adults showed a preference to obtain information through technologically‐based formats (e.g., websites, social media), whereas early adults used a wider range of formats (e.g., websites, booklets). Awareness of and access to genetic information prior to genetic clinic attendance is needed. A review of the utility of current resources available for at‐risk young adults would be helpful.